Antioxidant activity of medicinal plants used in phytotherapy - Kéry, Á.; Blazovics, A.; Fejes, Sz.; Nagy, É.; Lugasi, A.; Kursinszki, L.; Czinner, E.; Kristó, T. Sz.; Apáti, P.; Balázs, A.; Szőke, E. (International Journal of Horticultural Science, 2001)
Oxygen free radicals play an important role in the development of different disorders like inflammatory-immune injury, carcinogenesis, hepatic toxicity and artherosclerosis. The antioxydant role of a wide spectrum of natural products has been established. Flavonoids and other phenolic compounds (proanthocyanidins, rosmarinic acid, hydroxicinnamic derivatives, catechines, etc.) of plant origin have been reported as scavengers and inhibitors of lipid peroxidation. We have studied the antioxidant activity as well as content and composition of natural phenolics in a series of medicinal plants with phytotherapeutical significance. Thus we determined the total phenol contents and studied the composition of flavonoids, polyphenols, phenolic acids of different vegetative and reproductive organs of medicinal plants: Anthriscus cerefolium (L.) Hoffm., Petroselinum crispum L., Cichorium intybus L., Helichrysum arenarium D.C.„cempervivum tectorum L., Taravacum officinale Web. Characteristic constituents in the various crude drugs were determined by chromatographic (TLC, HPLC) and spectroscopic (UV, UV-VIS) methods. The non specific scavenger activities of the medicinal plant extracts were studied by the chemiluminometric technique. The changes of chemiluminescence intensity of the H,G,•0H-luminol system at increasing concentrations of the H702/ -OH were measured. Inhibitory effects of selected standardized fractions from plants were tested on ascorbic acid induced lipid peroxidation in rat liver and homogenates. The best correlation were established with total phenolics in some medicinal plants (S. tectorum, T. officinale) while activities in other cases seem to be influenced by flavonoids (P. crispum, H. arenarium, A. cerefolium) and by hydroxicinnamic derivatives (C. intybus).